Sex‐related differences in outcomes among men and women under 55 years of age with acute coronary syndrome undergoing percutaneous coronary intervention: Results from the PROMETHEUS study. Issue 4 (24th May 2016) - Chandrasekhar, Jaya; Baber, Usman; Sartori, Samantha; Faggioni, Michela; Aquino, Melissa; Kini, Annapoorna; Weintraub, William; Rao, Sunil; Kapadia, Samir; Weiss, Sandra; Strauss, Craig; Toma, Catalin; et al.
Abstract : Background: Young women undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) experience greater adverse events than men, potentially due to under‐treatment. We sought to compare the 1‐year outcomes by sex in patients ≤55 years of age from a contemporary PCI cohort. Methods: PROMETHEUS was a retrospective multicenter observational US study comparing outcomes in clopidogrel and prasugrel treated patients following ACS PCI. MACE was defined as a composite of death, myocardial infarction, stroke or unplanned revascularization. Clinically significant bleeding was defined as bleeding requiring transfusion or hospitalization. Hazard ratios were generated using multivariable Cox proportional hazards regression. Results: The study cohort included 4, 851 patients of which 1, 162 (24.0%) were women and 3, 689 (76.0%) were men. In this cohort, the prevalence of diabetes (41.0 vs. 27.9%) and chronic kidney disease (12.7 vs. 7.2%) was higher among women compared with men. Irrespective of sex, prasugrel was used in less than one‐third of patients (31.8% in men vs. 28.1% in women, P  = 0.01). Unadjusted, 1‐year MACE (21.1% vs. 16.2%, P  < 0.001) and bleeding (3.6% vs. 2.2%, P  = 0.01) was significantly higher in women compared with men, but these results were no longer significant after adjustment for risk (HR 1.13, 95% CI 0.94–1.36 for MACE and HR 1.31, 95% CI 0.85–2.04 for bleeding). Conclusion: Women ≤ 55 years of age undergoing ACS PCI have significantly greater comorbidities than young men. Despite a higher risk clinical phenotype in women, prasugrel use was significantly lower in women than men. Female sex was associated with a significantly higher risk of 1‐year MACE and bleeding than male sex, findings that are attributable to baseline differences. © 2016 Wiley Periodicals, Inc.